PRESENTATION OF HORIZONTAL MOVEMENTS OF THE EARTH’S CRUST BY RESULTS OF GEODESIC MEASUREMENTS: PRESENTATION OF HORIZONTAL MOVEMENTS OF THE EARTH’S CRUST BY RESULTS OF GEODESIC MEASUREMENTS - Yanchev, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The subject of the study is to present a modern model of local horizontal movements of the Earth’s crust in a fault zone with appropriate accuracy and representativeness through the results of precise GNSS measurements on a geodynamic site to analysis and evaluation of modern local geodynamic processes occurring in fault zones.